2018
DOI: 10.5796/electrochemistry.17-00082
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Ti(III) Ions in a KF–KCl Eutectic Melt

Abstract: The electrochemical behavior of Ti(III) ions in a eutectic KF-KCl molten salt was investigated using cyclic voltammetry, square wave voltammetry, and chronoamperometry at 923 K. Ti(III) ions were produced by the addition of 0.50 mol% of K 2 TiF 6 and 0.33 mol% of Ti sponge to the melt. The reduction of Ti(III) ions to metallic Ti was observed as a single 3-electron wave around 0.33 V vs. K + /K in the square-wave voltammogram. The electrodeposition was conducted at a Mo electrode by galvanostatic electrolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…The potential was more negative than 0.4 V vs. K + /K from which the reduction current of Ti(III) to Ti metal was observed. 21 The potential is more negative at higher current density. Particularly, the potential becomes more negative than 0.25 V during the beginning at 100 mA cm −2 .…”
Section: Morphology Of Electrodepositedmentioning
confidence: 98%
“…The potential was more negative than 0.4 V vs. K + /K from which the reduction current of Ti(III) to Ti metal was observed. 21 The potential is more negative at higher current density. Particularly, the potential becomes more negative than 0.25 V during the beginning at 100 mA cm −2 .…”
Section: Morphology Of Electrodepositedmentioning
confidence: 98%
“…Although the environmental impact of fluorine is significant, a solution containing Ti ions is favorable for stable applications. 123) Norikawa et al 124,125) investigated the electrochemical deposition of Ti in a KFKCl molten salt at 923 K. Approximately 0.1 mol% K 2 TiF 6 and an excess amount of Ti sponge were added to this water-soluble salt, indicating the electrochemical deposition of Ti metal from Ti 3+ . Dense and smooth films of Ti with 20 µm thickness were obtained.…”
Section: Deposition From Fluoride Meltmentioning
confidence: 99%
“…Based on these reports, we have focused on the electrodeposition of titanium in fluoride-chloride mixtures consisting of single cations and having enough fluoride concentrations (14)(15)(16)(17). We have already reported the electrochemical behaviors of Ti(III) ions and the electrodeposition of Ti in molten KF-KCl (45:55 mol%, 923 K) (14)(15)(16) and LiF-LiCl (45:55 mol%, 923 K) (17). We found that LiF-LiCl has an advantage for electrodepositing smooth Ti films due to its lower melting point (774 K at the eutectic composition (18)).…”
Section: Introductionmentioning
confidence: 99%